A clinical study of patients with conservatively managed extra dural hematoma at a tertiary care hospital - Mohammed Minhajuddin Harsoori; Arvind Kumar Tyagi; Mayukh Kamal Goswami (Creative Pharma Assent, 2023)
Background: Head injury causes accumulation of blood between the rigid skull and the outer endosteal layer of the dura mater. If the volume of extradural hematoma is less than 30 ml volume, it may not require surgery based on neurological examination. Objectives: To study the various causes, factors influencing and outcome of conservatively management in Extra Dural Hematomas. Materials and Methods: A total of 23 Extra Dural Hematoma cases requiring conservative management were included in the study. All the patients were subjected to complete neurological examination including and various imaging techniques like CT brain and chest X-ray. The patients with volume<30ml, thickness<5 mm, midline shift<5 mm, GCS >8, were subjected to conservative management by admitting the patients in Intensive Care Units (ICU). Results: Among 23 EDH cases, 17 (74%) cases were males and 6(26%) cases were females. The mean age of patients was 26.7years. Road traffic accident was the common mode of injury in 47.8% (11 cases) of patients. Mean volume of hematoma was 20.5ml and GCS Score was mild to moderate group.The majority of the patients (34.7%) presented with frontal EDH. Among 23 cases, 91.3% of the patients were discharged with good recovery. Conclusion: Extra Dural Hematoma (EDH) with low volume can be considered for conservative therapy by close observation, yet a risk of sudden neurological deterioration. However, surgical evacuation is the definitive treatment of EDH but craniotomy can be avoided in many patients with keen observation and repeated neurological assessments.